ChemInform Abstract: Metal‐Free Oxidative Lactonization of Carbohydrates Using Molecular Iodine. Issue 47 (4th November 2013) - Fusaro, Maxime B.; Chagnault, Vincent; Josse, Solen; Postel, Denis
Abstract An operationally simple protocol is developed for the oxidation of lactols to lactones by molecular iodine.